The stranger in the lifeboat : a novel - Albom, Mitch (New York : Harper, 2021)
A group of shipwreck survivors pull a mysterious man from the water who claims to be God, leading to a spiritual and emotional reckoning.
Keywords: Shipwreck survival -- Fiction; Faith -- Fiction